Sustaining a warm corona in active galactic nucleus accretion discs. Issue 4 (27th June 2020) - Ballantyne, D R; Xiang, X
ABSTRACT: Warm coronae, thick (τT  = 10–20, where τT is the Thomson depth) Comptonizing regions with temperatures of ∼1 keV, are proposed to exist at the surfaces of accretion discs in active galactic nuclei (AGNs). By combining with the reflection spectrum, warm coronae may be responsible for producing the smooth soft excess seen in AGN X-ray spectra. This paper studies how a warm corona must adjust in order to sustain the soft excess through large changes in the AGN flux. Spectra from one-dimensional constant density and hydrostatic warm corona models are calculated assuming that the illuminating hard X-ray power law, gas density, Thomson depth, and coronal heating strength vary in response to changes in the accretion rate. We identify models that produce warm coronae with temperatures between 0.3 and 1.1 keV, and measure the photon indices and emitted fluxes in the 0.5–2 and 2–10 keV bands. Correlations and anticorrelations between these quantities depend on the evolution and structure of the warm corona. Tracing the path that an AGN follows through these correlations will constrain how warm coronae are heated and connected to the accretion disc. Variations in the density structure and coronal heating strength of warm coronae will lead to a variety of soft excess strengths and shapes in AGNs. A larger accretion rate will, on average, lead to a warm corona that produces a stronger soft excess, consistent with observations of local Seyfert galaxies.